A Detailed Study: Does the Luangwa Hippo Population Size and Density Distribution Vary between Upper and Lower Study Blocks? What Are the Management Implications of Such Distribution Pattern? - Chansa Chomba; Twakundine Simpamba; George Kampamba; Vincent Nyirenda (International Research in Environment, Geography and Earth Science Vol. 9, 2021)
The pattern of population distribution of the common hippopotamus was examined along the 165 km stretch of the Luangwa River in eastern Zambia. The rise and fall in population size create oscillations which have persisted in the last 40 years (1976-2015). The study area was divided between the upper (A - D) and lower (E - H) study blocks. Population data collected between 1976 - 2015 showed a significant difference in the pattern of density distribution between upper and lower study blocks. Upper blocks had higher density of 41/km than lower blocks 29/km. Length of study blocks and mortality were discounted as density was used to determine distribution pattern, while mortality applied to both river segments and was insignificant. These results suggest that primary production in each study block as influenced by river geomorphologic features such as river bends and confluences characterized higher hippopotamus density in the upper blocks. The present study also found that hippopotamus pasture was mainly restricted to the alluvial belt which had in some places vast grasslands such as the Nsefu Plains in the upper river segment. Further research is required to investigate other factors that may have interplayed with food (above ground grass biomass) and river meander features to separate upper and lower blocks.